The climate change–water–energy nexus and its impacts on urban livelihoods in Zimbabwe - Reid, Memory (My University, 2021)
Climate change is predicted to greatly impact Southern African countries, largely due to variability in temperature and precipitation. These variations affect urban population livelihoods as well as water and energy security due to a heavy reliance on hydropower for energy. Using the Kariba sub-basin of the Zambezi River Basin, this study examines the possible impacts of hydroclimatic variations on future water and energy security in Zimbabwe. Over 50 years of hydroclimatic and hydropower output data was combined with data from surveys of informal businesses reliant on electricity to generate information on the vulnerability of urban livelihoods to energy insecurity in Zimbabwe. Interviews with key informants were used to understand the roles of various government institutions in climate change mitigation, water resource management, energy and the informal sector. Results of hydroclimatic patterns showed a general warming and drying trend for the Kariba sub-basin, variability in Zambezi River runoff and reduced hydropower output over time. Hydroclimatic variables impacted hydropower generation, confirming a climate change-water-energy nexus. Household survey data revealed home-based informal businesses across all socio-economic backgrounds, heavily reliant on an unstable electricity supply. Poor households were disproportionately affected by the unstable electricity supply because they could not afford alternative energy sources to continue business during power cuts. This highlighted the vulnerability of poor urban populations and their diminished capacity to adapt to climate change induced stresses. It was established that while national governmental bodies provided overall leadership on climate change issues, they also created an enabling environment for Small and Medium Enterprises through enacting laws and legislation. Climate trends and energy insecurity add to these complexities as marginalised groups fail to adapt to the impacts of energy insecurity on their livelihoods. This study highlighted the importance of exploring and cultivating a range of energy options to sufficiently mitigate against the impacts of climate change on access to energy and on urban livelihoods. Energy mixes that do not depend only on climate sensitive technology like hydropower should be iv considered. Furthermore, governments need to play a direct, gender-specific role in an informal sector dominated by women with limited bargaining power for the growth of their businesses.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2021